Kolaborasi Guru dan Orang Tua dalam Mengatasi Moralitas dan Karakter Negatif Siswa Era Game Online Free Fire di Kelas V SDN 61 Bengkulu Tengah - Anisa Apri Norma Handayani; Ali Akbar Jono; Lukman Lukman (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The morality and character of students who use excessive free fire online games tend to be negative, characterized by irresponsible characters, lack of empathy and tend to behave aggressively. This study aims to determine the collaboration of teachers and parents in overcoming the negative morality and character of students in the Free Fire online game era at SDN 61 Bengkulu Tengah. Using descriptive qualitative methods, with homeroom teachers, parents and students as informants, through observation, interviews and documentation. Data analysis techniques through data reduction, data presentation, drawing conclusions and verification. Data validity uses source triangulation, technique triangulation, and time triangulation. The results of the study show that: (1) Collaboration between teachers and parents in overcoming negative morality and character in students in the era of the Free Fire online game, namely by teachers actively involving parents through meetings and distributing report cards to communicate children's learning problems, and discussing solutions to overcome negative morality and character, building shared awareness about the negative impacts of games through meetings and discussions; (2) The impact of the online game Free Fire on students' morals and character is a decline in moral and character values, lack of empathy, lack of responsibility, and aggressive behavior; (3) The condition of students after playing the online game Free Fire, students are not concentrated and not focused on studying, tend to ignore schoolwork, and are not motivated to achieve academic achievement; (4) Actions taken to overcome negative morality and character of those addicted to the free fire online game are active collaboration between the school and parents, the school provides extracurricular activities such as scouts, dance, and sports to divert students' attention from the influence of online games. Meanwhile, parents limit game playing time, monitor children's game activities, communicate with the school, and encourage children to do physical activities and positive activities. Thus it can be concluded that the collaboration of teachers and parents can overcome the morality and negative character of students in the era of the free fire online game. So it can be suggested to be able to overcome the morality and negative character of the free fire online game era, then increase the collaboration between teachers and parents in schools.Keywords: Collaboration of Teachers and Parents, Morality and Negative Character, Era of Free Fire Online Games. Abstrak: Moralitas dan karakter siswa yang menggunakan game online free fire yang berlebih cenderung negative, ditandai dengan karakter kurang tanggungjawab, kurang empati dan cenderung berperilaku agresif. Penelitian ini bertujuan untuk mengetahui kolaborasi guru dan orang tua dalam mengatasi moralitas dan karakter negative siswa era game online Free Fire di SDN 61 Bengkulu Tengah. Menggunakan metode kualitatif deskriptif, dengan informan guru wali kelas, orang tua dan siswa, melalui observasi, wawancara dan dokumentasi. Teknik analisis data melalui reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Keabsahan data menggunakan triangulasi sumber, triangulasi teknik, dan triangulasi waktu. Hasil penelitian menunjukan bahwa: (1) Kolaborasi guru dan orang tua dalam mengatasi moralitas dan karakter negative siswa era game online Free Fire yaitu dengan cara guru aktif melibatkan orang tua melalui rapat dan pembagian rapot untuk mengkomunikasikan permasalahan belajar anak, dan berdiskusi mencari solusi mengatasi moralitas dan karakter negatif, membangun kesadaran bersama tentang dampak negatif game melalui pertemuan dan diskusi; (2) Dampak yang ditimbulkan dari game online Free Fire terhadap moral dan karakter siswa yaitu penurunan nilai moral dan karakter, kurang empati, kurang tanggung jawab, dan bersikap agresif; (3) Kondisi siswa setelah main game online Free Fire, siswa tidak konsentrasi dan tidak fokus belajar, cenderung mengabaikan tugas sekolah, dan tidak termotivasi untuk mencapai prestasi akademik; (4) Tindakan yang diberikan dalam mengatasi moralitas dan karakter negative yang kecanduan game online free fire yaitu berkolaborasi aktif antara pihak sekolah dan orang tua, sekolah menyediakan kegiatan ekstrakurikuler seperti pramuka, tari, dan olahraga untuk mengalihkan perhatian siswa dari pengaruh game online. Sedangkan orang tua membatasi waktu bermain game, memantau aktivitas game anak, menjalin komunikasi dengan pihak sekolah, serta mendorong anak melakukan kegiatan fisik dan kegiatan positif. Dengan demikian dapat disimpulkan bahwa kolaborasi guru dan orang tua dapat mengatasi moralitas dan karakter negative siswa era game online free fire. Sehingga dapat disarankan untuk dapat mengatasi moralitas dan karakter negative era game online free fire, maka tingkatkan kolaborasi antara guru dan orang tua di sekolah.Kata kunci: Kolaborasi Guru dan Orang Tua, Moralitas dan Karakter Negatif, Era Game Online Free Fire.